(3GdeaGgje h GdfeGPL h GdeOGNd GdYdejIs - (3eLOj YhV(B, (3eHGQcs ((3GQHO(B:s (3YGde GdcJH GdMOjK(B,s, 2009)
(3fTCI GdQjGOI h JWhQgG (B: (3GdeaGgje h GdJYQjaGJ , GdeOGNd GdYdejI dOQGSI XGgQI GdQjGOI , efgLjI GdHMK GdYdej aj GdQjGOI , GdYedjI GdQjGOjI , ETcGdjI GdQjGOI h feGPLgG GdeNJdaI aj GdMOK GdQjGOj, GdefXeGJ GdQjGOjI , GdQjGOI GdeDSSjI , GdQjGOI GdOhdjI , JLGQH YGdejI aj GdQjGOI , JfejI h JWhjQ GdQjGOI aj HjFI GdCYeGd GdCQOfjI (B: (3GaJQGVGJ h JUhQGJ ebJQMI ddeSJbHd (B.s
(3eQGLY U(B.369 (3; GdLOGh d U(B.(3e ; GdGTcGd U(B.(3fs
Keywords: (3EOGQI GdCYeGds; (3GdEHJcGQGJs; (3GdPcGA(B- (3GdEOGQjs